Overruling Mahkamah Konstitusi RI terkait Isu Korupsi - Zaka Firma Aditya (The Constitutional Court of the Republic of Indonesia, 2021)
Overruling is a revision of a court’s previous judicial precedent, meaning the court replaces the precedent with a new rule. This article sees that overruling is legitimate to seek constitutional truth. In practice, the Constitutional Court of the Republic of Indonesia (CCRI) has overruled its own Decisions through judicial review. This article focuses on the CCRI’s overruling on corruption issues which are the status of the Indonesian Corruption Eradication Commission and the meaning of the phrase “may harm State’s financial” which is stated in Law No. 31 of 1999. This article argues that those Decisions are consistent with constitutional truth although the ratio decidendi of the Court of the latter issue is inadequate. A case approach and a conceptual approach are used in the analysis of this legal research.